ANALISIS KUALITAS LAYANAN JASA PENDIDIKAN TERHADAP KEPUASAN MAHASISWA PADA POLITEKNIK NEGERI SRIWIJAYA - Yahya Yahya (Politeknik Negeri Sriwijaya, 2013)
The objective of the research was to examine the impact of education’s service quality toward student’s satisfaction of State Polytechnic of Sriwijaya Palembang. Primary data was collected through survey technique from 96 samples, respondents taken by random sampling method and was analysed by using technique of multiple regression. The result indicated that service quality which was implemented had been running well of which caused the student’s satisfaction was quiet enough. Through statistical analysis, service quality which consisted of: reliability, responsiveness, assurance, emphaty, and tangibles variables had a positive influence toward student’s satisfaction. But in partial reliability, responsiveness, and emphaty had not a positive influence. Those above results of analysis indicated that management of State Polytechnic of Sriwijaya have to improve the assurance, and tangibles. Mean while of reliability, responsiveness, and emphaty have to be restrained and more over to be raised in the future